(untitled) (Perner’s Contacts, 2016)
The article deals with the analysis of rail transport accidents in the period of 2008 – 2015 and with the comparison of their causes. The existence of a relationship between causes of accidents and calendar months when the accidents have occurred was determined by using one-way analysis of variance.